Wasatiyyah dalam Al-Qur’an: Landasan Teologis dan Pedagogis untuk Pembelajaran PAI yang Responsif Terhadap Tantangan Ekstremisme Agama - Tarmidi Tarmidi; Sanuri Sanuri (Khulasah : Islamic Studies Journal, 2026)
This article examines the concept of wasatiyyah in the Qur’an as a theological foundation and pedagogical framework for developing Islamic Religious Education (PAI) that is responsive to the challenges of religious extremism among the youth. Utilizing a qualitative approach based on thematic exegesis (mawdū‘ī tafsir) analysis and a synthesis of recent academic literature (2020–2026), this study reveals that wasatiyyah is not merely a normative discourse or a social diplomacy strategy, but rather an epistemological paradigm structured around four operational pillars: tawassuth (the middle path), tawāzun (balance), i‘tidāl (objective justice), and tasāmuḥ (active tolerance). Theologically, this concept serves as a systemic antidote to selective-textual interpretations and identity dichotomies that act as entry points for radicalization. Pedagogically, wasatiyyah demands a radical transformation in PAI learning: shifting from an indoctrinative-dogmatic model toward a dialogical, critical, and contextual approach aligned with maqāṣid al-sharī‘ah. The formulated implementation strategies include the development of Religious Critical Media Literacy (RCML), the mapping of student vulnerabilities, the strengthening of an inclusive school ecosystem based on a whole-school approach, and a holistic evaluation that measures the internalization of moderation values. An empirical study in elementary schools within Lelea District confirms that integrating moderation values through daily habits, teacher role-modeling, nationalism-religiosity collaboration, and extracurricular activities effectively builds ideological resilience and an inclusive character. This article recommends a measurable reconstruction of the PAI curriculum, the enhancement of teacher competence in critical pedagogy and hermeneutical exegesis, and the synchronization of education policies that position religious moderation as a verifiable outcome. These findings contribute to the decolonization of Islamic educational epistemology and provide an applicable operational framework for practitioners, curriculum developers, and policymakers in the digital era.